In-situ grown metal-organic framework derived CoS-MXene pseudocapacitive asymmetric supercapacitors. (April 2023) - Adil, M.; Olabi, Abdul Ghani; Abdelkareem, Mohammad Ali; Alawadhi, Hussain; Bahaa, Ahmed; ElSaid, Khaled; Rodriguez, C.
Abstract: Since 2D MXene offers high conductivity and high redox-active sites making it an excellent candidate for supercapacitors (SCs). On the other hand, metal-organic frameworks (MOF) derived 3D nanospheres like CoS have their own distinctive merits such as high porosity, abundant active sites, large surface area, and superior electrochemical properties. Herein, a novel strategy has been opted to fabricate MXene cobalt sulfide (MXene-CoS). For the first time MOF derived CoS nanostructures were successfully incorporated with MXene flakes and grown on porous nickel foam. Consequently, the electroactivity of the as-prepared electrodes was enhanced by dwindling the ion-electron diffusion pathways. MXene-CoS/AC asymmetric device operated at a wide potential window of 1.6 V which is among the widest for MXene based SCs. The prepared electrodes demonstrated ultra-high specific capacity of 447 mA h g −1 at a current density of 3 mA cm −2 . The assembled MXene-CoS/AC ASC solid-state device manifested a high specific capacity of 190 mA h g −1 and volumetric capacity of 1.2 mA h cm −3 at a current density of 2 mA cm −2 . The presented strategy paves a way for a new dimension of MOF-derived metal sulfides incorporated with 2D MXene for high-performance SCs with excellent cyclic stability. Highlights: A novel strategy has been opted to fabricate MXene cobalt sulfide (MXene-CoS). MXene-CoS demonstrated high electrochemical activity and superior stability. MXene-CoS/AC asymmetric device exhibited outstanding performance and stability.